English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Part (A):
Use the Composite Rule to differentiate the function
g(x) = SQRT(1+x^2)

Part(B):
Use the Composite Rule and your answer to part(A) to show that the function
h(x)=ln{x+SQRT(1+x^2)} has derivative
h'(x)=1/SQRT(1+x^2)

Right I think the answer to part(A) is g'(x)=x/SQRT(1+x^2), am I right??
But I can't figure out part(B) does anyone know how to do that part using the answer to part(A)??

2006-09-18 11:27:45 · 2 answers · asked by tomhafiz 1 in Science & Mathematics Mathematics

2 answers

Part (A):
g(x) = SQRT(1+x^2)
g'(x) = (1/2) (1+x^2)^(-1/2) (2x)
g'(x) = x/(1+x^2)^(1/2) or x/SQRT(1+x^2)

Part (B):
h(x)=ln{x+SQRT(1+x^2)}
h(x)=ln{x+g(x)}
h'(x)=(1/x+g(x)) (1+(x/(1+x^2)^(1/2)))
h'(x)= (1+x^2)^(-1/2)
h'(x)=1/SQRT(1+x^2) (Proven)

2006-09-18 15:54:01 · answer #1 · answered by Kemmy 6 · 0 0

g(x)=(1+x^2)^(1/2)
g'(x)=1/2(1+x^2)^(-1/2)*d(1+x^2)
g'(x)=1/2(1+x^2)^(-1/2)*(2x)
simplify
g'(x)=x/((1+x^2)^1/2)

2006-09-18 11:49:57 · answer #2 · answered by hr1hc 2 · 0 0

fedest.com, questions and answers